EFFECTS OF AIRCRAFT NOISE ON RESIDENTIAL PROPERTIES RENTAL VALUE AROUND MAIDUGURI INTERNATIONAL AIRPORT, BORNO STATE, NIGERIA - YAKUBU ALI, ANDESIKUTEB; AYUBA, BITRUS; INNOCENT IKO, ISAAC; ADAMU LUCAS, DONATUS (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
This study examined the effects of aircraft noise on residential properties rental value around Maiduguri International Airport Area in Borno State. The data was collected through the administration of 363 structured questionnaire to selected household heads residing in the neighbourhoods around the airport. It utilized mean ranking, the simple regression analysis to analyze the data collected. The result of the simple regression analysis revealed that aircraft noise negatively influences residential property value around the airport and that aircraft noise does not really depreciate residential property rental value, the noise level for the day-eveningnight time depends on frequency of flights as well as distance from the airport and the time of the day and also showed that rental values of residential properties in the study area fall within the range of 50,000 Naira and below for one room apartment. The study also found that tenants are willing to stay in the neighbourhood due to the presence of Air Force Base (security personnel) in the area. The study therefore recommends among other things, that investors and property developers embarking on property development should take into account the effects of noise on rental value of residential property to avoid wasting of funds in such ventures, also upgrading of the sound insulation of buildings will be a useful technique for reducing the negative impacts of aircraft noise to enhance the quality of urban life of residents. Government through urban development board should ensure the enforcement of land use and physical planning laws to mitigate and minimize the negative impacts of airport noise in the airport areas.